2010
DOI: 10.1123/ijsnem.20.5.418
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Mineral Density and Other Features of the Female Athlete Triad in Elite Endurance Runners: A Longitudinal and Cross-Sectional Observational Study

Abstract: Low bone-mineral density (BMD) is associated with menstrual dysfunction and negative energy balance in the female athlete triad. This study determines BMD in elite female endurance runners and the associations between BMD, menstrual status, disordered eating, and training volume. Forty-four elite endurance runners participated in the cross-sectional study, and 7 provided longitudinal data. Low BMD was noted in 34.2% of the athletes at the lumbar spine, and osteoporosis in 33% at the radius. In cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 37 publications
6
59
4
1
Order By: Relevance
“…Some medical professionals have suggested that all female elite endurance athletes be screened with DXA because of the increased risk for impaired bone health in that population [54]. DXA provides information about BMD and composition and serves as a proxy for bone health [55].…”
Section: Prevention Of Stress Fractures In Female Athletesmentioning
confidence: 99%
“…Some medical professionals have suggested that all female elite endurance athletes be screened with DXA because of the increased risk for impaired bone health in that population [54]. DXA provides information about BMD and composition and serves as a proxy for bone health [55].…”
Section: Prevention Of Stress Fractures In Female Athletesmentioning
confidence: 99%
“…However, only four studies assessing prevalence of all three Triad components have been conducted since the 2007 ACSM update [17,[19][20][21], and even then they did not all operationalize the constructs of the Triad according to the 2007 ACSM standard (see Table 1.1). One of these four studies, conducted by Schtscherbyna et al [21] in a sample of 78 elite female swimmers (mean age = 14.6 years, SD = 2.0 years), did not incorporate the concept of energy availability into the measurement of prevalence, assessing only disordered eating using three validated written measures of disordered eating risk.…”
Section: Prevalencementioning
confidence: 99%
“…Pollock et al [20] assessed the prevalence of the conditions of the Triad in a sample of 44 elite female endurance runners (mean age 22.9 years, SD = 6.0 years). BMD was measured at several locations on the body, with Z-scores varying by location.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Low energy availability impairs skeletal health by uncoupling the turnover of bone in a manner that lowers bone mineral density over time (Christo et al, 2008;De Souza et al, 2008;Pollock et al, 2010). Like other tissues, bone is constantly turning over as osteoclast cells resorb old bone and osteoblast cells form new bone.…”
mentioning
confidence: 99%